Collector size effect on the measurement of applied water depth from irrigation systems - Wiens, Scott Wade (Kansas State University, 2010)
Center pivot irrigation systems are used in crop production across the state of Kansas. The American Society of Agricultural and Biological Engineers (ASABE) standard on uniformity testing of a center pivot system calls for collectors to be used to measure the water depth emitted by the irrigation system. The standard was designed without specially considering the low pressure sprinklers now commonly used on center pivot systems; the recommended collectors may not accurately measure the applied depth from these sprinklers. The collector size effect on measured water depth and measured depth variability was studied for spinning plate, fixed plate, and wobbling plate sprinkler systems. Five different collector sizes (C2 (5.5 cm), C4 (10.0 cm), C6 (14.8 cm), C8 (20.0 cm), and C10 (27.4 cm)) were studied using four 5x5 Latin squares. Each collector’s water depth was measured and statistically analyzed. Two analysis of variance (ANOVA) tests of the collector size effect were reported. Past experimental results were compared to this experiment’s results. The ANOVA for the measured water depth reported no collector size effect for the spinning plate and wobbling plate systems. The ANOVA of the variability of measured depths showed significant differences between collector sizes for the spinning plate system but not for the wobbling plate system. Previous studies of spinning plate and wobbling plate systems reported acceptable variability for all collector sizes. Although some collector sizes measured significantly different mean depths, the numerical difference in mean depths was small. Any studied collector size could be used to measure the water depth of wobbling plate systems, but the C4 collector is ideal. C4 and C6 collectors are ideal for measuring spinning plate systems. Significant differences between measured depths were reported for the fixed plate system. The C10 measured significantly lower water depths than all other collectors, and the C4 collector measured lower depths than the C2 and C8 collectors. The variability of mean depths was similar and high for all collector sizes. Previous experiments also indicated that different collector sizes measured different depths and had high variability of depth measurements for the fixed plate sprinkler systems. The distinct stream pattern provides a challenge for accurately measuring the water depth with these collector sizes; other methods of measuring uniformity should be considered for fixed plate sprinklers.
Keywords: Irrigation; Uniformity; Rain gauge; Collector size; Sprinklers; Engineering, Agricultural (0539)